Selective attention and emotional interference in adults who stutter: Evidence from Stroop tasks - Aydoğuş, Merve; Tunçer, Aylin Müge (Karger, 2025)
Introduction Stuttering encompasses complex cognitive, behavioral, and emotional mechanisms that interact dynamically. Clarifying the multidimensional nature of stuttering is fundamental to both its conceptual understanding and the advancement of evidence-based treatment. This study aimed to investigate cognitive and emotional interference in adults who stutter (AWS) and explore its relationship with anxiety levels, stuttering frequency, and the psychosocial impact of stuttering. Methods Fifty AWS and fifty age- and sex-matched fluent controls participated in this study. Data were collected using the Stroop TBAG test, the Emotional Stroop test, the Wright and Ayre Stuttering Self-Rating Profile (WASSP-TR), the State-Trait Anxiety Inventory (STAI), and stuttering frequency measures. Descriptive, comparative, and correlational analyses were conducted using SPSS version 25. Results The AWS demonstrated significantly longer completion times on the Stroop task than fluent speakers. In the Emotional Stroop task, they also exhibited prolonged reaction times to stuttering-related and threat-related words, while reaction times to neutral words did not differ significantly between the groups. State anxiety was significantly associated with both attention measures, whereas stuttering frequency was correlated specifically with selective attention. Conclusions The findings indicate that AWS differ significantly from fluent controls in their performance on tasks requiring selective attention and exhibit an attentional bias toward emotionally salient stimuli. These results underscore the relevance of cognitive and emotional processes in stuttering and support the integration of anxiety- and attention-related dimensions into clinical assessment and therapy planning.
Keywords: Stuttering; Attentional bias; Selective attention; Anxiety; Emotional Stroop